Spatial analysis of renewable-based hybrid district heating possibilities in a Hungarian rural area - Csontos, Csaba; Soha, Tamás; Harmat, Ádám; Campos, José; Csüllög, Gábor; Munkácsy, Béla (International Journal of Sustainable Energy Planning and Management, 2020)
This paper investigates the possibilities of establishing renewable-based “hybrid district heating” (HDH) applications in a peripheral rural area of Hungary, the Bükkalja. This particular region struggles with energy poverty, severe import dependency and serious air pollution. Considering natural and social capabilities, Danish and Austrian experiences, potential sites for rural district heating developments were examined. Door-to-door field surveys, residential heat demand, GIS-based renewable energy potential calculations, detailed supply-demand and statistical analysis were applied to reveal HDH possibilities. Most of the results have a tight correlation with the Heat Roadmap Europe’s relevant values (PETA 4.3), however, in case of suggestions, there are considerable differences. The outcomes also highlight that current biomass utilization far exceeds the sustainability limits within the area. The screening proves that the capabilities of seven rural settlements are suitable for HDH developments. This investigation supports the decision-making process and its proposed projects could play a significant role in the local energy transition. This study underlines that rural HDH developments could have the same relevance as similar projects in urban circumstances.